Genetic diversity and differentiation of Mongolian and Russian yak populations - Xuebin, Q.; Han Jianlin; Lkhagva, B.; Chekarova, I.; Badamdorj, D.; Rege, J.E.O.; Hanotte, Olivier H. (Wiley, 2005)
In this study we examined the genetic diversity of yak populations in the northernmost part of their current global distribution. Five Mongolian and one Russian yak populations as well as one Chinese yak population from the Qinghai-Tibetan Plateau, the putative centre of yak domestication, were analysed with 15 microsatellite loci to determine the level of genetic variation within populations as well as the genetic differentiation and relationship between populations. A total of 116 microsatellite alleles were identified. The mean number of alleles per locus (MNA) across populations was 7.73 +- 1.98 and the mean expected heterozygosity (HE) was 0.696 +- 0.026. The relative magnitude of gene differentiation (FST) among populations was 4.1%, and all genetic differentiations (FST) between populations were significant (p < 0.001). A significant inbreeding effect (FIS) was detected in the Hovsgol yak (p < 0.01). There was no indication of a recent bottleneck in any of the populations studied. The results showed that yak populations in Mongolia and Russia have maintained high genetic diversity within populations and a low, although significant, genetic differentiation between populations. Both phylogenetic and principal component analyses support a close genetic relationship between the Gobi Altai, south Gobi and north Hangai populations, and between the Hovsgol and Buryatia populations respectively. Our results indicate that these yak populations should be considered as distinct genetic entities in respect of conservation and breeding programmes.